Anti-amyloidogenic properties of 5‑caffeoylquinic acid-capped selenium nanoparticles - Shubhangi D. Shirsat; Chunyi Li; Zhipeng Liu; Varenyam Achal; Olivier Habimana (Scientific Reports)
Abstract The advancement of neuroprotective pharmacological agents to proficiently avert amyloid-β (Aβ) clustering persists as a significant obstacle in Alzheimer’s disease (AD) management. This analysis focuses on the inhibitory characteristics related to amyloid formation of selenium nanoparticles (SeNPs) enveloped in 5-caffeoylquinic acid (CQA), which are biosynthesized using violet sweet potato (PSP) extract. Engineered SeNPs revealed an absorption peak at 260 nm, were spherical and non-crystalline (50–60 nm), and had a zeta potential measured at 24.3 ± 2.1 mV. The antioxidant traits of SeNPs were showcased (IC50 = 8.01 ± 1.21 µg/mL), by obstructing AChE (IC50 = 3.70 ± 0.02 µg/mL) and BChE (IC50 = 72 ± 0.5 µg/mL), while also diminishing Aβ fibrillation, thereby emphasizing their function in the modulation of amyloid clustering. Molecular dynamics simulations elucidated that CQA-SeNPs preferentially associate with hydrophobic residues (e.g., Leu34 and Phe19) of the Aβ peptide, obstructing β-sheet formation. These findings suggest that CQA-SeNPs interfere with Aβ aggregation, offering a potential therapeutic strategy for AD.